Work engagement as a mediator between perceived internal corporate social responsibility and deviant behaviour: The moderating effect of gender - Surya, Juanda; Prastiawati, Fitriani (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2026)
This study examines the role of work engagement in mediating the relationship between perceived internal corporate social responsibility (CSR) and workplace deviant behavior, with gender as a moderating variable. The research focuses on employees working in banking companies. Data were collected from 183 employees of banking institutions through an online survey questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that perceived internal CSR has a positive and significant effect on work engagement. This finding suggests that organizational practices that prioritize employee welfare, such as fair treatment, career development opportunities, and work–life balance, can strengthen employees’ psychological attachment to their work. When employees perceive that their organization genuinely cares about their well-being, they tend to develop stronger dedication, energy, and involvement in their work. Furthermore, the findings reveal that internal CSR has a negative and significant effect on deviant behavior. This result indicates that employees who perceive their organization as socially responsible are less likely to engage in counterproductive behaviors that may harm the organization. Work engagement is also found to have a negative and significant effect on deviant behavior, suggesting that employees who are more engaged in their work tend to avoid behaviors that violate organizational norms. In addition, the mediation analysis demonstrates that work engagement partially mediates the relationship between internal CSR and deviant behavior. However, the moderating role of gender is not supported, indicating that the influence of internal CSR in reducing deviant behavior is relatively consistent across male and female employees in the banking sector. Overall, the findings highlight the importance of internal CSR as a strategic organizational resource for fostering employee engagement and minimizing workplace deviance.